ANALISIS SEGMENTASI PASAR TERHADAP HARGA SEPEDA MOTOR AUTOMATIC YAMAHA MIO PADA PT . HASJRAT ABADI KOTAMOBAGU - PAPUTUNGAN, INDRIYATI; Tumbel, Tinneke M.; Tarore, Henny S. (JURNAL ADMINISTRASI BISNIS, 2017)
By lookong at the development of a motorcycle thar is increasingly rapidly, many manufacturers of the new motor started to go to indonesia. The large number of the new motor started to go to indonesia. The large number of existing motorcycle company raises competitive. Pressure on industi motorcycle Consumer needs and desires are very multiform against type or brand of motorcycles then request the community againts motorcycles continue to experience increased, therefore, marketin krekatif and put the market strategy, take advantage of opportunities that arise in the market related to the desires of the commonity therefore companies should set the price according to the quality of the product because the price setaffect the quantity sold is because the price of the very influential towards the success of the products marketed by the company. The aim in this study is whether there is a connection between the market segmentation with the price of motorbikes and detect other factorsthat also affect the market share within the company bike motors. This research is quantitative reseacrch using a simple linear regression analysis approach. Engineering data collection done by spreading the questionnaire filled by 75 respondents and analyzed using simple regression analysis and use test results from t. Linear regression analysis is a simple variabel market segmentation neffect against prices. Hypothesis test andresults showedthat thevariables simultaneo usly influential market segmentation significantly to price. Based on the results of this research, companies Yamaha Indonesia to make the latest innovations inaccordance withthe community's lifestyle and always give you the design and the latest models in accordance with advances automotive world. Keywords : Market segmentation, Pricing